Online Marketing Training in the Digital Era to Increase Income for Residents of Kebayoran Lama District - Tarmizi, Achmad; Shieto, S. (Golden Ratio of Community Services and Dedication, 2025)
Through practical digital marketing training, this community service program aimed to empower residents of Jalan Pulo Kemuning, RT 003 RW 015, South Jakarta. Many participants, including micro-entrepreneurs and homemakers, previously relied on traditional promotion methods and lacked exposure to digital tools. The program introduced them to essential platforms such as Instagram, WhatsApp Business, and Shopee, while also enhancing skills in content creation and online branding. Implemented using a participatory approach, the training involved hands-on practice, mentoring, and post-training support. The results showed increased digital literacy, improved self-confidence, and early signs of expanded market reach and sales growth among participants. While infrastructure limitations and time constraints were noted, the program's overall impact was positive and promising. This initiative reflects the role of higher education institutions in bridging digital gaps and supporting inclusive economic development through community engagement and applied knowledge transfer.